Tecnologias digitais e redes interativas - Alves, Waldir Antonio (2009)
This work aims to explore the conceptual boundaries and the different meanings of collective action, in its history, current prospects of whom is, involving a process of establishment of the senses of propositions on the ideas of sharing / collaborating with human cognition. The field of collective intelligence in the network is relevant to this work because it is a genuine expression of an affluent intelligence. The various forms of virtual communities, the P2P strategy, mobile communities, the virtual libraries, the explosion of blogs and wikis and the Orkut fever are proof that cyberspace is a crucial factor in enhancing the social and cultural capital available and it deserves a detailed study. The hability to converge to share thoughts to an affluent action of a collective intelligence may be questionable as intelligence, whether we do not take into account the ethical issue of its intent. The collective intelligence may be a new form of planning of the power, tool that can be used for actions that not always smarts or ethical. These issues were discussed assuming the ideas developed by Castells, Lévy and Rheingold, among other authors. Being the computer a media that allows the creation and simulation, in addition to opening new connections, it structure with a new way of thought and a new genre of knowing, as they were worked in this research